Danger! Negative memories ahead: the effect of warnings on reactions to and recall of negative memories. Issue 3 (16th March 2021) - Bridgland, Victoria M. E.; Takarangi, Melanie K. T.
ABSTRACT: A trigger warning is an alert that upcoming material containing distressing themes might "trigger" the details and emotion associated with a negative memory to come to mind. Warnings supposedly prevent or minimise this distress. But, do warnings really have this effect? To simulate the experience described above, here, we examined whether warning participants—by telling them that recalling a negative event would be distressing—would change characteristics associated with the immediate and delayed recall of a negative event (such as phenomenology e.g., vividness, sense of reliving), compared to participants who we did not warn. Generally, we found that time helps to heal the "emotional wounds" associated with negative memories: negative characteristics—such as emotion, vividness etc.—faded over time. However, the event's emotional impact (the frequency of experiences related to the event such as "I had trouble staying asleep"), subsided less over a two-week delay for participants who were warned in the first session. Our findings suggest that warning messages may prolong the negative characteristics associated with memories over time, rather than prepare people to recall a negative experience.